Determinan Perilaku Merokok Elektrik (VAPE) pada Remaja Menurut Theory of Planned Behavior - Annisa Deliana; Luqman Effendi (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2026)
The smoking problem is one of the significant global health challenges, with a tobacco epidemic in Indonesia. A concerning phenomenon at present is the increasing prevalence of smoking among adolescents, as well as the growing popularity of electronic cigarets or vapes as a supposedly safer alternative. The purpose of this study is to analyze the determinants of electronic smoking behavior in adolescents using the Theory of Planned Behavior (TPB) approach. The research method for this study is a Systematic Literature Review, which utilizes databases including PubMed, Google Scholar, and published journals. This research is taken from sources from the last 10 years and was conducted in November-December 2025. The results of this study indicate that e-cigarette smoking behavior in adolescents is significantly influenced by the three main components of the TPB: attitude toward the behavior, subjective norms, and perceived behavioral control. The main conclusion is the need for a comprehensive strategy that involves strengthening the role of families, educating about health hazards, and implementing stricter smoke-free zone regulations and advertising restrictions to protect the future health of adolescents.